Healthcare Associate Infection in Different Departments of a Tertiary Care Hospital in Bangladesh - Farzin, Anika; Goutam, Arpita; Neeva, Nahla Islam; Akter, Kajol; Khan, Md Taifur Aziz; Jahan, Tarana; Hossain, Md Tanvir (Eastern Medical College Journal, 2024)
Background: Healthcare-associated infections (HAIs), which occur when a patient is receiving care in a hospital or other healthcare facility, are the most frequent adverse events in healthcare worldwide. This study aimed to find the causative bacterial agents of HAI from different clinical samples in different departments. Materials &Methods: This was a cross-sectional descriptive study conducted in the department of Microbiology & Virology, Sylhet MAG Osmani Medical College, in collaboration with in-patient departments of Sylhet MAG Osmani Medical College hospital from January 2019 to December 2019with ethical clearance from respective IERB. A total of 123 patients of different age, sex was enrolled in this study. Samples were collected from postoperative wounds, post catheterized urinary tract infections, diabetic wounds and intravenous cannula from Surgery, Medicine and Obstetrics & Gynecology ward. Standard laboratory procedures were applied to isolate and identify the bacteria. Results: Among 123 patients 46 (37.4%) were affected by hospital acquired infections. Higher prevalence (n=28, 60.87%) of HAI was found in the Surgery ward and the lower prevalence (n=9, 19.56%) was found in Medicine and Obstetrics & Gynecology ward. The difference in the frequency of growth and no growth in samples collected from these departments was almost the same. The most common type of infection was surgical wound infection (43.48%). Staphylococcus aureus (28.26%), Pseudomonas aeruginosa (17.39%) and E. coli (13.04%) were the primary causes of healthcare-associated infections. Conclusion: Irrespective of all circumstances, HAI is a burden now-a-days for healthcare professionals. So proper knowledge about the rate of its occurrence and the reasons should be found to control its burden. Through monitoring and proper implementation of IPC can help us to control this situation. Eastern Med Coll J. July 2024; 9 (2): 105-109